An energy efficient authenticated key agreement protocol for SIP-based green VoIP networks. (January 2016) - Zhang, Liping; Tang, Shanyu; Zhu, Shaohui
Abstract: Voice over Internet Protocol (VoIP) is spreading across the market rapidly due to its characteristics such as low cost, flexibility implementation, versatility of new applications, etc. However, the voice packets transmitted over the Internet are not protected in most VoIP environments, and then the user׳s information could be easily compromised by various malicious attacks. So an energy-efficient authenticated key agreement protocol for Session Initial Protocol (SIP) should be provided to ensure the confidentiality and integrity of data communications over VoIP networks. To simplify the authentication process, several protocols adopt a verification table to achieve mutual authentication, but the protocols require the SIP server to maintain a large verification table which not only increases energy consumption but also leads to some security issues. Although several attempts have been made to address the intractable problems, designing an energy-efficient authenticated key agreement protocol for SIP-based green VoIP networks is still a challenging task. In this study, we propose an efficient authentication protocol for SIP by using smartcards based on elliptic curve cryptography. With the proposed protocol, the SIP server needs not to store a password or verification table in its database, and so no energy is required for the maintenance of the verification table. Security analysis demonstrates that the proposed protocol can resist various attacks and provides efficient password updating. Furthermore, the experimental results show that the proposed protocol increases efficiency in comparison with other related protocols. Highlights: We proposed an energy efficient authentication protocol for VoIP networks. No energy is required for the maintenance of verification tables in our protocol. Our protocol can resist various attacks and provides efficient password updating. The experimental results show that the proposed protocol increases efficiency.